Modeling of nanosecond pulsed laser processing of polymers in air and water. (14th May 2018) - Marla, Deepak; Zhang, Yang; Hattel, Jesper H; Spangenberg, Jon
Abstract: Laser ablation of polymers in water is known to generate distinct surface characteristics as compared to that in air. In order to understand the role of ambient media during laser ablation of polymers, this paper aims to develop a physics-based model of the process considering the effect of ambient media. Therefore, in the present work, models are developed for laser ablation of polymers in air and water considering all the relevant physical phenomena such as laser–polymer interaction, plasma generation, plasma expansion and plasma shielding. The current work focuses on near-infrared laser radiation ( λ = 1064 nm) of nanosecond pulse duration. The laser–polymer interaction at such wavelengths is purely photo-thermal in nature and the laser–plasma interaction is assumed to occur mainly by inverse-bremsstrahlung photon absorption. The computational model is based on the finite volume method using the Crank−Nicholson scheme. The model predicts that underwater laser ablation results in subsurface heating effect in the polymer and confinement of the laser generated plasma, which makes it different from laser ablation in air. Plasma expansion velocities are much lower in water than in air. This results in an enhanced plasma shielding effect in the case of water. The predicted results of ablation depth versus fluence from the model are in qualitative agreement with those observed in experiments.